Multimodal Imaging of Waldenstrom Macroglobulinemia-Associated Hyperviscosity-Related Retinopathy Treated with Plasmapheresis - Michael J. Schatz; Carl S. Wilkins; Oscar Otero-Marquez; Toco Y. P. Chui; Richard B. Rosen; Meenakashi Gupta (Case Reports in Ophthalmological Medicine)
While plasmapheresis is well known to significantly improve both retinal findings and systemic manifestations associated with Waldenstrom macroglobulinemia, few reports exist documenting changes in optical coherence tomography angiography (OCT-A). The authors present a case of a patient with Waldenstrom macroglobulinemia who had resolution of white-centered peripheral retinal lesions and parafoveal outer nuclear layer hyperreflective material following plasmapheresis. Applying image analysis software to before and after OCT-A images, the authors were able to show an objective decrease in retinal capillary and large vessel density following plasmapheresis. This technique can be used to guide treatment and surveillance for patients with hyperviscosity-related retinopathy.